KEANEKARAGAMAN JENIS GASTROPODA DI HUTAN MANGROVE DESA MENDALOK KECAMATAN SUNGAI KUNYIT KABUPATEN MEMPAWAH - Herviory, Efrosina Yelni; Anwari, M Sofwan; Yani, Ahmad (JURNAL HUTAN LESTARI, 2019)
Gastropod is a single-shelled animal that walks using stomach for their legs. Mangrove forest located Mendalok village, Sungai Kunyit sub-district, Mempawah district have pristine mangroves whose function is still maintained and is natural. The purpose of this study was to examine the diversity of Gastropoda species in Mendalok the area. Data retrieval the diversity of Gastropod species, the researchers empolyed a purposive sampling method that making each zone used 3 lines observation of each one line transect. While the three observation tracks consist of the Avicenia zone, Rhizopor zone, Bruguiera zone. The number of Gastropod individual found was 367 with 5 families and 8 species (Cerithideopsilla alata, littorina obstutata, Littorinopsis anguliferis, Littoraria melanstoma, Graciliclva costata, Casidulla aurisfelis, Ellobium aurisjudae, and Lirttoraria undulata). The research found diversity indexes in Avicennia zone = 2,98, Rhizopora zone = 3,05 and Bruguiera zone = 1,16. Especially, the highest density is in the type of Gastropod Littoraria undulata. Additionally, the dominant index is found in the Avicenia zona = 0,8562, the Rhizopora zone = 0, 5410 and Bruguiera zone = 0,4585. While the low similarity index exist in both Bruguiera zone = 28,77 % and Avicenia zone = 28,50%, and the index of type similarity is at the value of 0,1117.Keyword: Ecotourism of mangrove, Gastropods, mangrove forests.